First report of a papillomavirus-induced viral plaque in the mouth of a dog - Munday JS; Hobson P; Bell CM (John Wiley and Sons Ltd on behalf of ESVD and ACVD, 2025)
Canis familiaris papillomavirus type 16 was amplified from a mass in the mouth of a dog. The mass was histologically consistent with a pigmented viral plaque. This is the first report of an oral viral plaque in a dog. Histological investigation is essential to allow differentiation from an oral melanoma.
Keywords: dog; oral; papillomaviruses; pigmented plaque; viral oncogenesis; viral plaque